Facile Iodine Detection via Fluorescence Quenching of β‐Cyclodextrin:Bimane‐Ditriazole Inclusion Complexes. Issue 3 (28th December 2020) - Pramanik, Apurba; Karmakar, Joy; Grynzspan, Flavio; Levine, Mindy
Abstract: Reported herein is the detection of iodine using a non‐covalent association complex formed between a β‐cyclodextrin host and a designer bimane ditriazole guest. This complex responds to the presence of iodine with a marked decrease in the observed fluorescence signal. A sub‐nanomolar detection limit of this system in the solution‐state was determined. Moreover, results using filter paper onto which the β‐cyclodextrin‐bimane complex was adsorbed show a noticeable advantage compared to the cyclodextrin‐free bimane. Thus, highly sensitive on‐paper colorimetric iodine detection was achieved. Abstract :